Strategi Koping untuk Permasalahan Harga Diri Rendah dalam Pandangan Islam dan Medis - Subagja, Reva; Kamila, Alda Humaimah; Zalianty, Revalina; Anindia, Sharfina; Nofelinda, Shelfiana; Supriyadi, Tedi; Faozi, Akhmad (Innovative: Journal Of Social Science Research, 2025)
Low self-esteem is a feeling towards oneself, while problems with poor interpersonal relationships and associated with low anxiety, low affectivity, so that low self-esteem is associated with nursing can cause self-esteem in groups and acceptance of others as valuable in life. High negative self-esteem towards oneself causes loss of self-confidence, pessimism, and is not at risk of depression and schizophrenia, so that negative feelings fundamentally cause loss of self-confidence and self-esteem of individuals and self-esteem disorders (Muhith, 2016). Low Self-Esteem In Islamic teachings, self-esteem (muru'ah) has a very important meaning. Islam teaches its people to maintain self-esteem and dignity, which are considered part of faith. Some key concepts in Islam related to self-esteem include: 'Izzah (Self-Glory): Is a concept that emphasizes the importance of having dignity and honor. In Islam, one must draw closer to Allah to obtain 'izzah, which is a source of glory. Muru'ah: This refers to maintaining self-respect and commendable behavior. Imam Ghazali emphasized that muru'ah is an important attribute in personal transformation, where individuals with high muru'ah will act in accordance with good moral values. 'Iffah (self-restraint): this concept is related to self-control and commendable behavior. Maintaining 'iffah is part of an effort to maintain self-esteem. (Ministry of Religion, 2021) Riskesdas in 2018 stated that 6.7% of the Indonesian population experienced low self-esteem and the highest prevalence was in Yogyakarta with a figure of 10.4%. Research conducted by Aryanyi and Khodijah in 2023 on "The Relationship between Self Esteem and Gratitude: A Review of the Hadith Narrated by Sunan Al-Tirmidhi No. Index 2034 Psychological Perspective" explains that realizing the concept of gratitude can be an implication that individuals have high self-esteem, while individuals who do not realize the concept of gratitude have low self-esteem. Furthermore, in a study conducted by Oktaviana and Aprilliana in 2024 entitled "The Effect of Cognitive Behavioral Therapy (CBT) on Adolescents Experiencing Low Self-Esteem: a systematic review." explains that CBT has an influence in increasing self-esteem in adolescents who have low self-esteem problems. Islam offers spiritual and moral solutions, while medicine offers psychological and clinical solutions. The disciplines of Islamic and medical views provide a new perspective in dealing with the problem of low self-esteem in each individual. The purpose of this study is to describe and integrate two disciplinary views to analyze coping strategies in Islamic and medical views for patients with low self-esteem. The relevance of Islam and medicine can be integrated holistically to be applied to the problem of low self-esteem.